PENGARUH PENGGUNAAN TEKNOLOGI DIGITAL DAN SOFT SKILL TERHADAP KESIAPAN KERJA SISWA MPLB DI SMKN 1 SIDIKALANG - Wella Christina Situmorang; Rotua Sahat Pardamean Simanullang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of digital technology use and soft skills on the work readiness of grade XI Office Management and Business Services (MPLB) students at SMK Negeri 1 Sidikalang. The background of this research is based on the fact that most students still face limitations in mastering office software and lack confidence in soft skills such as communication, teamwork, and time management, which negatively affect their work readiness.This research employed a quantitative approach with an ex post facto method. The population consisted of 72 grade XI MPLB students, while the sample comprised 36 students from class XI MPLB 2, selected using purposive sampling. Data were collected through questionnaires tested for validity and reliability, and analyzed using multiple linear regression with the help of SPSS.The results of the study show that: (1) digital technology use has a positive and significant effect on students’ work readiness with a t-value of 3.589 and a significance level of 0.001 < 0.05; (2) soft skills have a positive and significant effect on students’ work readiness with a t-value of 8.916 and a significance level of 0.000 < 0.05; and (3) simultaneously, digital technology use and soft skills significantly affect work readiness with an F-value of 63.622 and a significance level of 0.000 < 0.05. The coefficient of determination (R Square) is 0.648, indicating that 64.8% of the variance in work readiness is explained by both independent variables, while the remaining 35.2% is influenced by other factors.In conclusion, mastering digital technology and improving soft skills are crucial factors in preparing students to face the demands of the workforce.